Writing the Erasure of Emotions in Dystopian Young Adult Fiction: Reading Lois Lowry’s The Giver and Lauren Oliver’s Delirium - Davis, Rocío G. (Narrative Works, 2014)
Young Adult (YA) dystopian fiction blends the traditional developmental narrative with a heightened concern with issues regarding the individual against society, often in the context of a post-apocalyptic world. In this article, I examine the way Lois Lowry’s The Giver (1993) and Lauren Oliver’s Delirium (2011) focus on the state’s regulation over or removal of their people’s emotions and decisions in the context of the representation of future societies. If we consider the place of emotions in YA literature in general, with its interest in adolescents’ interaction with their families, each other, their school, or other communities, we can accept the validity of emotions as a prism through which to examine the text’s didactic and social purposes. Specifically, by deploying a discourse that emphasizes the dangerous consequences of unbridled emotions in earlier historical times, dystopian texts ask us to think about the political potential of feelings as catalysts for social change.